Cardiovascular events associated with nicorandil administration prior to primary percutaneous coronary intervention in patients with acute ST-segment elevated myocardial infarction: a systematic review and meta-analysis. Issue 6 (3rd June 2019) - Li, Jiaying; Xu, Xiaoming; Zhou, Xinbin; Dai, Jin; Ma, Lan; Chen, Chen; Li, Xinyao; Mao, Wei
ABSTRACT: Introduction : Nicorandil may exert cardioprotective effects in ischemic heart disease. However, its efficacy in combination with early reperfusion is uncertain. The authors performed a meta-analysis of the short- and long-term clinical outcomes of nicorandil administration at the time of primary percutaneous coronary intervention (PCI) in patients with ST-elevated myocardial infarction (STEMI). Methods : PubMed, MEDLINE, Embase, and the Cochrane Library databases were systematically searched for eligible randomized controlled studies. The primary endpoint was major adverse cardiovascular events (MACE), both in-hospital and post-discharge. The secondary endpoint was the incidence of no-reflow phenomenon. Results : Ten studies were included ( n = 1105). Mean patient age was 63.0 ± 10.0 years; 76.6% of patients were male. Compared with controls who received primary PCI, combined nicorandil/primary PCI significantly reduced in-hospital MACE (pooled odds ratio [OR] 0.16; 95% confidence interval [CI] 0.09–0.27), follow-up MACE (pooled OR 0.53; 95% CI 0.37–0.75), and total MACE (pooled OR 0.27; 95% CI 0.15–0.49). The combined treatment also reduced the incidence of no-reflow phenomenon (pooled OR 0.34; 95% CI 0.23–0.50). Conclusion : Nicorandil administration at the time of primary PCI is associated with reduced MACE (both short- and long-term) and no-reflow phenomenon in patients with STEMI.